GROWTH CYCLES IN MATURE AND DUAL ECONOMIES - Skott, Peter (Práticas de Administração Pública, 2022)
Mature economies may experience fluctuations, but the average medium and long run growth rate matches the natural rate. Like Kaldor's neo-Keynesian models, the Marx-Goodwin tradition explains this outcome by endogenizing the distribution of income and assuming that the accumulation of capital is increasing as a function of the profit share. The application of Goodwin cycles to developing economies may be hard to justify, however. The modified Goodwin models in this paper include relative-wage norms as a central element of wage formation. Norms change endogenously, leading to path dependence (hysteresis) in the stationary solution for the employment share of the modern sector. The effects of shocks – the sensitivity of the long-run outcome to initial conditions – may be amplified by non-linearities in the adjustment of wages to deviations of actual wages from the norm.